Marriage and Housework - Cristina Borra; Martin Browning; Almudena Sevilla (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
This paper provides insights into the gains of forming a couple by estimating how much of the difference in housework between single and married individuals is causal and how much is due to selection. Permanent unobserved heterogeneity explains about half of the observed differences in housework documented in the cross-sectional data. Further ancillary evidence suggests that individuals with a higher preference for marriage also have more traditional views on the division of household labour. There remains a genuine half-an-hour increase per week in housework time for each partner, with women specializing in routine and men in non-routine housework tasks.
Keywords: D13; J12; J22; 330; Marriage; Time use; Home production